Preparation method and application of manganese fluoride / carbon nanofiber composite material
The preparation of manganese fluoride/carbon nanofiber composite materials through electrospinning technology solved the thermodynamic and dynamics of the potassium ion battery electrode materials, and achieved electrochemical performance with high capacity, long life and excellent rate performance.
Patent Information
- Application Number
- CN202510062048.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
AI Technical Summary
The existing potassium ion battery electrode materials have insufficient thermodynamic and dynamics, resulting in low potassium storage capacity, poor cycle stability and poor rate performance.
Electrospinning technology is used to make a manganese fluoride/carbon nanofiber composite material into a manganese fluoride/carbon nanofiber composite material, and manganese fluoride nanoparticles are generated through the calcination process, which are uniformly dispersed in the carbon nanofibers.
It improves the electrochemical performance of manganese fluoride/carbon nanofiber composite materials, achieves high capacity, long life and excellent rate performance, and is suitable for the negative electrode material of potassium ion batteries.
Smart Images

Figure CN119877152A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a fluoride composite material, and in particular to a preparation method and application of a manganese fluoride / carbon nanofiber composite material. Background Art
[0002] In recent years, lithium-ion batteries (LIBs) have achieved great commercial success with their long cycle life and high energy density. However, disadvantages such as low content in the earth's crust, uneven geographical distribution, and high cost limit the application of LIBs in large-scale energy storage. Therefore, it is of great significance to explore new energy storage systems to replace expensive LIBs. Potassium-ion batteries (PIBs) are becoming a promising alternative to LIBs due to their relatively abundant potassium resources, high operating voltage, and comparable energy density. However, K + radius Bili + and Na + Many materials suitable for inserting lithium or sodium become difficult to insert potassium or become unstable due to large volume changes during the inserting and removing process. Therefore, the development of new electrode materials for potassium ion batteries becomes the key.
[0003] Transition metal oxides have been widely studied as high-capacity conversion anodes for LIBs (e.g., a theoretical capacity of 756 mAh g -1 Low-cost MnO) is used in PIBs, but their application in PIBs is rare. In addition, transition metal fluorides with relatively high conversion voltages are usually regarded as cathode materials in LIBs. When the Gibbs free energy change (ΔG) of potassium storage is calculated, the positive value of MnO indicates that the conversion reaction is non-spontaneous and unsuitable for battery systems. Therefore, the researchers turned to another spontaneous conversion material, MnF2, which is also low-cost and has a theoretical capacity of up to 577 mAh g -1 It is worth mentioning that the calculated redox potential of MnF2 is above 2 V in LIBs, making it suitable for use as a cathode. In PIBs, however, the voltage provided by MnF2 is only 1.692 V. The thermodynamic difficulties of potassium storage in metal fluorides may bring new opportunities for their application in anodes.
[0004] However, ideal anode materials require thermodynamically low redox potentials and fast reaction kinetics. The large band gap and high ionization degree of metal fluoride bonds usually lead to poor electronic conductivity of fluorides. In addition, the huge volume change of the conversion reaction may lead to the repeated destruction and formation of a thick solid electrolyte interface (SEI), hindering the K + Diffusion of ions. Summary of the invention
[0005] Purpose of the invention: The purpose of the present invention is to provide a method for preparing a manganese fluoride / carbon nanofiber composite material having excellent specific capacity, cycle performance and rate performance;
[0006] The second object of the present invention is to provide an application of the manganese fluoride / carbon nanofiber composite material prepared by the above method.
[0007] Technical solution: The method for preparing the manganese fluoride / carbon nanofiber composite material of the present invention comprises the following steps:
[0008] (1) dissolving a metal salt and a fluorine-containing polymer material in an organic solvent to obtain a precursor solution;
[0009] (2) obtaining nanofibers by electrospinning the precursor solution in step (1), and drying to remove the solvent;
[0010] (3) calcining the nanofibers after removing the solvent in an inert atmosphere to obtain a manganese fluoride / carbon nanofiber composite material.
[0011] Wherein, the metal salt in step (1) is at least one of manganese acetylacetonate, manganese acetate or manganese nitrate.
[0012] Wherein, in step (1), the fluorine-containing polymer material is polyvinylidene fluoride and / or polyvinylidene fluoride-hexafluoropropylene copolymer. Wherein, in step (1), the concentration of the fluorine-containing polymer material is 100 to 150 g L -1 ; The concentration of metal salt is 0.1~0.3 mol L -1 Too high or too low a concentration of fluorine-containing polymer materials will make the viscosity of the precursor solution too high or too low, making it difficult to use for subsequent electrospinning; too high a concentration of metal salts will make it difficult to form a uniform and stable solution, while too low a concentration will reduce the content of active substances in the carbon fibers.
[0013] Wherein, in the step (1), the molar amount of the metal salt and the mass ratio of the fluorine-containing polymer material is 2 to 6 mol / kg. If the ratio is too high, the size of the manganese fluoride nanoparticles in the carbon nanofiber will be too large, while if the ratio is too low, the active fluoride content in the carbon fiber will be low, which is not conducive to the utilization of the potassium storage capacity.
[0014] The electrospinning rate in step (2) is controlled at 0.4-0.6 mL / h. -1 ; The working voltage is 15-25kV. If the feed rate is too high, the uniformity of the spinning fiber will decrease, while if it is too low, the production efficiency will decrease; if the working voltage is too high, the spinning fiber will be thinned, while if it is too low, it will be difficult to form fibers.
[0015] The calcination temperature in step (3) is 450-550° C. When the temperature is lower than 450° C., the fluorine-containing polymer material is difficult to be completely decomposed and carbonized, and when the temperature is higher than 550° C., the manganese fluoride particles in the carbon nanofibers will grow and the nanofiber structure will be destroyed.
[0016] The drying temperature in step (2) is 120-150° C. When the temperature is lower than 120° C., the solvent evaporates slowly, causing fiber adhesion, and when the temperature is higher than 150° C., the fluorine-containing polymer is easily melted, destroying the fiber structure.
[0017] The manganese fluoride / carbon nanofiber composite material prepared by the above method is used as a negative electrode material for potassium ion batteries.
[0018] Principle of the invention: The present invention uses low-cost metal salts and fluorine-containing polymer materials as raw materials in the synthesis process, and makes them into nanofibers through electrostatic spinning. In the subsequent one-step calcination process, the fluorine-containing polymer material is pyrolyzed into carbon nanofibers, and serves as a fluorine source to make the metal salt generate manganese fluoride nanoparticles. The method has a simple synthesis process.
[0019] The method of the present invention can produce a composite material in which manganese fluoride nanoparticles are uniformly dispersed in carbon nanofibers. The material is conducive to the transmission of electrons between particles along the carbon nanofibers, greatly promoting the use of the material capacity, and improving the cycle stability and rate performance of the manganese fluoride / carbon nanofiber composite material. In addition, the structure of carbon nanofibers encapsulating nanoparticles also avoids direct contact between the electrolyte and the active material, reduces electrolyte side reactions, and improves coulomb efficiency. With metal fluoride as the negative electrode, KF is generated during the conversion reaction, which helps to form a KF-rich solid electrolyte interface film (SEI), further enhancing the cycle stability of the potassium ion battery.
[0020] Beneficial effects: Compared with the prior art, the present invention has the following significant effects: the manganese fluoride / carbon nanofiber composite material prepared by the method of the present invention has excellent electrochemical properties. As the negative electrode material of potassium ion battery, the sample has a good electrochemical performance at 0.1Ag. -1 The display below shows 407.4mAh g -l High capacity at 5Ag -1 The following has 252.1mAh g -1 Excellent rate performance, at 1Ag -1 The composite material has a long life of 5000 cycles and a capacity retention rate of up to 82.6%. Therefore, the composite material in which manganese fluoride nanoparticles are uniformly dispersed in carbon nanofibers has great application potential as a high-performance and low-cost negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of the electrospinning device used in the present invention;
[0022] Figure 2 The XRD spectrum of the manganese fluoride / carbon nanofiber composite material prepared by the present invention;
[0023] Figure 3 The SEM and TEM images of Example 1 of the present invention are shown;
[0024] Figure 4 This is the thermogravimetric analysis curve of Example 1 of the present invention;
[0025] Figure 5 The materials of Example 1 and Comparative Example 1 of the present invention are in 0.1Ag -1 Charge and discharge curves under current density;
[0026] Figure 6 is the rate performance of Example 1 of the present invention;
[0027] Figure 7 For Example 1 of the present invention, at 0.1Ag -1 Cycling performance under current density;
[0028] Figure 8 The material of Example 1 of the present invention is 1Ag -1 Cycling performance diagram under current density;
[0029] Fig. 9 This is a cryo-TEM image of the material after cycling in Example 1 of the present invention;
[0030] Fig.10 These are the SEM and TEM images of Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0031] The present invention is described in further detail below.
[0032] Example 1
[0033] like Figure 1 As shown, a method for preparing a manganese fluoride / carbon nanofiber composite material comprises the following steps:
[0034] (1) 3 mmol of manganese acetylacetonate and 1 g of PVDF were added to 10 mL of N,N-dimethylformamide (DMF), heated and stirred at 50 °C for 6 h to form a uniform solution;
[0035] (2) The solution obtained in step (1) was used for electrospinning, and the injection rate was controlled at 0.5 mL h -1 , the working voltage is 20 kV; the spun fibers are dried in an oven at 150°C for 1 h to remove the solvent;
[0036] (3) The spun fiber obtained in step (2) was placed in an argon atmosphere tube furnace at 5°C min-1 The temperature is raised to 450°C and calcined for 2 h, and the product is obtained after cooling.
[0037] Characterization of MnF / CNF Materials:
[0038] Figure 2 This is the XRD spectrum of the manganese fluoride / carbon nanofiber composite material synthesized by this method. The figure shows that each diffraction peak corresponds to the standard card PDF#83-2418 of R-MnF2, and the material is a pure compound.
[0039] The size, morphology and microstructure of the obtained manganese fluoride / carbon nanofibers were analyzed using SEM and TEM images. Figure 3 Figures a and b are SEM images of manganese fluoride / carbon nanofibers. The diameter of the nanofibers is about 500 nm, and the surface is composed of a large number of fine nanoparticles. Figure 3 The c and d in the figure are TEM images of manganese fluoride / carbon nanofibers, which show that manganese fluoride nanoparticles are uniformly dispersed in the carbon nanofibers, and the size of the nanoparticles is only about 8nm. The content of MnF2 in the composite material can be measured by thermogravimetric analysis to be 65.2%. Figure 4 shown.
[0040] Electrochemical performance test:
[0041] The manganese fluoride / carbon nanofibers prepared in this example were ground and mixed with carbon black and sodium carboxymethyl cellulose (CMC) at a mass ratio of 80:10:10, and the resulting uniform slurry was applied on a Cu foil and dried under vacuum at 80°C for 12 h. -1 Potassium bis(fluorosulfonyl)imide (KFSI) in 1,2-dimethoxyethane (DME) was used as the electrolyte for potassium ion batteries, and glass fiber and metallic potassium were used as the separator and counter electrode of potassium ion batteries, respectively. CR2032 batteries were used for the electrochemical performance test. The battery was assembled in a glove box filled with argon atmosphere, and the water and oxygen concentrations were both less than 0.1ppm. The constant current charge and discharge test of the battery was carried out at room temperature using a Blue Power CT2001A multi-channel battery test system at 0.01–3.0V (vs.K + / K) within a fixed voltage range. For specific performance, see Figures 5 to 8 .
[0042] Figure 5 The manganese fluoride / carbon nanofiber of Example 1 is 0.01-3.0V (vs.K + / K) voltage range, the current density is 0.1A g -1 , the reversible specific capacity reaches 404.8 mAh g -1 . Figure 6 The rate performance of Example 1 is 5Ag.-1 Still can reach 252.1mAh g -1 capacity. Figure 7 It shows that the capacity retention rate of Example 1 after 200 cycles is 92.7%. Figure 8 The cycle performance of Example 1 is shown in Figure 1. -1 It has a long life of 5000 cycles and a capacity retention rate of up to 82.6%. Fig. 9 This is a cryo-TEM image after the cycle of Example 1. The interface between the material and the SEI film is clear, and the SEI component contains more KF components. This result shows that manganese fluoride nanoparticles help form KF-rich SEI during the conversion reaction and stabilize the structure of SEI.
[0043] Example 2
[0044] A method for preparing a manganese fluoride / carbon nanofiber composite material comprises the following steps:
[0045] (1) 3 mmol of manganese acetylacetonate and 1 g of PVDF-HFP were added to 10 mL of DMF and heated at 50 °C with stirring for 6 h to form a uniform solution;
[0046] (2) The solution obtained in step (1) was used for electrospinning, and the injection rate was controlled at 0.4 mL h -1 , the working voltage is 25 kV; the spun fibers are dried in an oven at 120°C for 1 h to remove the solvent;
[0047] (3) The spun fiber obtained in step (2) was placed in an argon atmosphere tube furnace at 5°C min -1 The temperature is raised to 550°C and calcined for 2 h, and the product is obtained after cooling.
[0048] The structure characterization and electrochemical performance test of the prepared manganese fluoride / carbon nanofiber material were carried out in the same manner as in Example 1. The electrochemical performance test results are shown in Table 1.
[0049] Example 3
[0050] A method for preparing a manganese fluoride / carbon nanofiber composite material comprises the following steps:
[0051] (1) Add 6 mmol of manganese acetate and 1.5 g of PVDF into 10 mL of DMF and heat at 50 °C with stirring for 6 h to form a uniform solution;
[0052] (2) The solution obtained in step (1) was used for electrospinning, and the injection rate was controlled at 0.6 mL h -1 , the working voltage is 15 kV; the spun fibers are dried in an oven at 130°C for 1 h to remove the solvent;
[0053] (3) The spun fiber obtained in step (2) was placed in a nitrogen atmosphere tube furnace at 5°C min -1 The temperature is raised to 500°C and calcined for 2 hours, and the product is obtained after cooling.
[0054] The obtained material was subjected to structural characterization and electrochemical performance test in the same manner as in Example 1. The electrochemical performance test results are shown in Table 1.
[0055] Comparative Example 1
[0056] A method for preparing a manganese fluoride / carbon nanofiber composite material comprises the following steps:
[0057] (1) 8 mmol of manganese acetate and 1 g of PVDF were added to 10 mL of DMF and heated at 50 °C with stirring for 6 h to form a uniform solution;
[0058] (2) The solution obtained in step (1) was used for electrospinning, and the injection rate was controlled at 0.4 mL h -1 , the working voltage is 25 kV; the spun fibers are dried in an oven at 120°C for 1 h to remove the solvent;
[0059] (3) The spun fiber obtained in step (2) was placed in an argon atmosphere tube furnace at 5°C min -1 The temperature is raised to 550°C and calcined for 2 h, and the product is obtained after cooling.
[0060] Except for the difference in molar amount of manganese acetate from Example 2, the rest is the same as Example 2. The morphology and structure of the prepared manganese fluoride / carbon nanofiber material were characterized and the electrochemical performance was tested in the same manner as in Example 2. The morphology characterization results are shown in Fig.10 It can be seen that when the manganese source concentration is too high, that is, the molar amount of the manganese source and the mass ratio of the fluorine-containing polymer material are too high, the fiber uniformity prepared is very poor, and the potassium storage performance is significantly reduced compared with Example 1. The electrochemical performance test results are shown in Table 1.
[0061] Comparative Example 2
[0062] Commercial manganese fluoride nanoparticles:
[0063] The commercial manganese fluoride nanoparticles were structurally characterized and electrochemically tested in the same manner as in Example 1. The specific capacity, cycle stability and rate performance were far inferior to those in Example 1. The electrochemical performance test results are shown in Table 1.
[0064] Comparative Example 3
[0065] A method for preparing a manganese fluoride / carbon nanofiber composite material comprises the following steps:
[0066] (1) 3 mmol of manganese acetylacetonate and 0.5 g of PVDF were added to 10 mL of DMF and heated at 50 °C with stirring for 6 h to form a uniform solution;
[0067] (2) The solution obtained in step (1) was used for electrospinning, and the injection rate was controlled at 0.4 mL h -1 , the working voltage is 25 kV; the spun fibers are dried in an oven at 120°C for 1 h to remove the solvent;
[0068] (3) The spun fiber obtained in step (2) was placed in an argon atmosphere tube furnace at 5°C min -1 The temperature is raised to 650°C and calcined for 2 h, and the product is obtained after cooling.
[0069] Except for the calcination temperature, the rest is the same as Example 2. The morphology and structure of the prepared manganese fluoride / carbon nanofiber material were characterized and the electrochemical performance was measured in the same manner as in Example 2. The morphology was similar to that of Comparative Example 1. The electrochemical performance test results are shown in Table 1.
[0070] Comparative Example 4
[0071] Based on Example 1, the difference from Example 1 is that in step (1), manganese acetylacetonate is replaced by manganese sulfate. At this time, manganese sulfate cannot be completely dissolved and cannot form a uniform solution for electrospinning.
[0072] Comparative Example 5
[0073] Based on Example 1, the difference from Example 1 is that in step (1), PVDF is replaced by polytetrafluoroethylene. At this time, polytetrafluoroethylene cannot be completely dissolved and cannot form a uniform solution for electrospinning.
[0074] Comparative Example 6
[0075] A method for preparing a manganese fluoride / carbon nanofiber composite material comprises the following steps:
[0076] (1) 3 mmol of manganese acetylacetonate and 1 g of PVDF were added to 10 mL of DMF and heated at 50 °C with stirring for 6 h to form a uniform solution;
[0077] (2) The solution obtained in step (1) was used for electrospinning, and the injection rate was controlled at 0.4 mL h -1 , the working voltage is 25 kV; the spun fibers are dried in an oven at 180°C for 1 h to remove the solvent;
[0078] (3) The spun fiber obtained in step (2) was placed in an argon atmosphere tube furnace at 5°C min -1 The temperature is raised to 550°C and calcined for 2 h, and the product is obtained after cooling.
[0079] Except for the drying temperature being different from that in Example 2, the rest is the same as that in Example 2. The obtained manganese fluoride / carbon nanofiber material is characterized in morphology and electrochemical performance in the same manner as in Example 2. Its morphology is similar to that in Comparative Example 1, which is due to the fact that the drying temperature is too high, causing the PVDF to melt, thereby causing the manganese source to aggregate and grow. The electrochemical performance test results are shown in Table 1.
[0080] Comparative Example 7
[0081] Preparation of manganese fluoride / carbon nanofiber materials:
[0082] (1) 3 mmol of manganese acetylacetonate and 1 g of PVDF were added to 10 mL of DMF and heated at 50 °C with stirring for 6 h to form a uniform solution;
[0083] (2) The solution obtained in step (1) was used for electrospinning, and the injection rate was controlled at 0.5 mL h -1 , the working voltage is 10kV; the liquid is easily dripped during the spinning process and uniform fibers cannot be formed; the obtained spinning product is dried in an oven at 150°C for 1h to remove the solvent;
[0084] (3) The spinning product obtained in step (2) was placed in an argon atmosphere tube furnace at 5°C min -1 The temperature is raised to 450°C and calcined for 2 h, and the product is obtained after cooling.
[0085] Characterization of MnF / C nanofiber materials:
[0086] Except for the electrospinning process parameters being different from those in Example 1, the rest are the same as those in Example 1. The obtained manganese fluoride / carbon nanofiber material was characterized in morphology and structure and tested for electrochemical properties in the same manner as in Example 1. The fiber morphology was destroyed, and the manganese fluoride particles also aggregated and grew. The electrochemical properties test results are shown in Table 1.
[0087] Table 1 Electrochemical performance data
[0088]
Claims
1. A method for preparing a manganese fluoride / carbon nanofiber composite material, characterized in that: The following steps are involved: (1) dissolving a metal salt and a fluorine-containing polymer material in an organic solvent to obtain a precursor solution; (2) obtaining nanofibers by electrospinning the precursor solution in step (1), and drying to remove the solvent; (3) calcining the nanofibers after removing the solvent in an inert atmosphere to obtain a manganese fluoride / carbon nanofiber composite material.
2. The method for preparing the manganese fluoride / carbon nanofiber composite material according to claim 1, characterized in that: The metal salt in step (1) is at least one of manganese acetylacetonate, manganese acetate or manganese nitrate.
3. The method for preparing the manganese fluoride / carbon nanofiber composite material according to claim 1, characterized in that: The fluorine-containing polymer material in step (1) is polyvinylidene fluoride and / or polyvinylidene fluoride-hexafluoropropylene copolymer.
4. The method for preparing the manganese fluoride / carbon nanofiber composite material according to claim 1, characterized in that: The concentration of the fluorine-containing polymer material in step (1) is 100 to 150 g L -1 .
5. The method for preparing the manganese fluoride / carbon nanofiber composite material according to claim 1, characterized in that: The concentration of the metal salt in step (1) is 0.3 to 0.6 mol L -1 .
6. The method for preparing the manganese fluoride / carbon nanofiber composite material according to claim 1, characterized in that: In the step (1), the molar ratio of the metal salt to the mass ratio of the fluorine-containing polymer material is 2 to 6 mol / kg.
7. The method for preparing the manganese fluoride / carbon nanofiber composite material according to claim 1, characterized in that: In step (2), the electrospinning feed rate is controlled at 0.4 to 0.6 mL / h -1 , the working voltage is 15~25kV.
8. The method for preparing the manganese fluoride / carbon nanofiber composite material according to claim 1, characterized in that: In the step (3), the calcination temperature is 450-550°C.
9. The method for preparing the manganese fluoride / carbon nanofiber composite material according to claim 1, characterized in that: In the step (2), the drying temperature is 120-150°C.
10. Use of the manganese fluoride / carbon nanofiber composite material prepared by the method according to any one of claims 1 to 9 as a negative electrode material for a potassium ion battery.
Citation Information
Cited By
Preparation method and application of packaged electric heating phase change fiber with axial orientation conductive network
CN120138826A